Authorship trends in software engineering - Fernandes, João M. (2014)
This paper aims to examine authorship trends in software engineering, especially those related to the number of authors, of scientific publications. We collected and mined around 70.000 entries from DBLP for 122 conferences and journals, for the period 1971–2012, in order to process several bibliometric indicators. We provide evidence that the number of authors of articles in software engineering is increasing on average around +0.40 authors/decade. The results also indicate that until 1980, the majority of the articles have a sole author, while nowadays articles with 3 or 4 authors represent almost half of the total.